2010
DOI: 10.1038/cdd.2010.70
|View full text |Cite
|
Sign up to set email alerts
|

E2F-1 regulation by an unusual DNA damage-responsive DP partner subunit

Abstract: E2F activity is negatively regulated by retinoblastoma protein (pRb) through binding to the E2F-1 subunit. Within the E2F heterodimer, DP proteins are E2F partner subunits that allow proper cell cycle progression. In contrast to the other DP proteins, the newest member of the family, DP-4, downregulates E2F activity. In this study we report an unexpected role for DP-4 in regulating E2F-1 activity during the DNA damage response. Specifically, DP-4 is induced in DNA-damaged cells, upon which it binds to E2F-1 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…This is the first time that TFDP3 was reported to be expressed in breast cancer, although TFDP3 was reported to be present in U2OS, HEK293, H1288, MCF-7 and HeLa cell lines [13]. The question whether TFDP3 is expressed in other breast cancer cell lines or in normal breast cell lines, however, was still unanswered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first time that TFDP3 was reported to be expressed in breast cancer, although TFDP3 was reported to be present in U2OS, HEK293, H1288, MCF-7 and HeLa cell lines [13]. The question whether TFDP3 is expressed in other breast cancer cell lines or in normal breast cell lines, however, was still unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…TFDP3 was found to dimerize with E2F1 to inhibit the biological function of E2F1, which is involved in p53-dependent or independent cell apoptosis and cell proliferation [11,12]. The negative regulatory effect of TFDP3 on E2F1 was speculated to result from a sequence localized to the C-terminus rather than the DNA binding region [13]. Recently, TFDP3 and some other transcription regulators were found to have a critical role in the gene interaction network in breast cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the Drosophila model,49 analysis of transgenic Drosophilia expressing the pathogenic mutant forms of human LRRK2 gene, I1915T or G2019S, demonstrated that defective LRRK2 does not possess GTPase activity. The LRRK2 gene therefore derepressed miRNA-mediated inhibition of the transcription factors E2F1 and DP,48 which are involved in the control of cell cycle and survival,49,50 and thereby increased dopaminergic neuronal death.…”
Section: Mirnas and Lrrk2mentioning
confidence: 99%
“…Again, depending on the exact context, E2F/DP interactions can positively or negatively modulate DNA repair. For example, following DNA damage by a variety of agents, including doxorubicin, etoposide and UV radiation, the abundance of DP-4 protein is substantially increased, replacing other DP proteins in E2F-1-containing complexes (Ingram et al, 2011). As a result, the capacity of E2F-1 to bind target promoters is strongly reduced, which can result in downregulation of cell cycle regulatory and/or DNA repair genes.…”
Section: Role Of E2f/dp Interactions In Dna Repairmentioning
confidence: 99%